ICON‐O: The Ocean Component of the ICON Earth System Model—Global Simulation Characteristics and Local Telescoping Capability. (6th October 2022) - Korn, P.; Brüggemann, N.; Jungclaus, J. H.; Lorenz, S. J.; Gutjahr, O.; Haak, H.; Linardakis, L.; Mehlmann, C.; Mikolajewicz, U.; Notz, D.; Putrasahan, D. A.; Singh, V.; et al.
Abstract: We describe the ocean general circulation model Ico sahedral N onhydrostatic Weather and Climate Model (ICON‐O) of the Max Planck Institute for Meteorology, which forms the ocean‐sea ice component of the Earth system model ICON‐ESM. ICON‐O relies on innovative structure‐preserving finite volume numerics. We demonstrate the fundamental ability of ICON‐O to simulate key features of global ocean dynamics at both uniform and non‐uniform resolution. Two experiments are analyzed and compared with observations, one with a nearly uniform and eddy‐rich resolution of ∼10 km and another with a telescoping configuration whose resolution varies smoothly from globally ∼80 to ∼10 km in a focal region in the North Atlantic. Our results show first, that ICON‐O on the nearly uniform grid simulates an ocean circulation that compares well with observations and second, that ICON‐O in its telescope configuration is capable of reproducing the dynamics in the focal region over decadal time scales at a fraction of the computational cost of the uniform‐grid simulation. The telescopic technique offers an alternative to the established regionalization approaches. It can be used either to resolve local circulation more accurately or to represent local scales that cannot be simulated globally while remaining within a global modeling framework. Plain Language Summary: Ico sahedral N onhydrostatic Weather and Climate Model (ICON‐O) is a global ocean general circulation model that works on unstructured grids. It rests on novel numerical techniques that belong to the class of structure‐preserving finite Volume methods. Unstructured grids allow on the one hand a uniform coverage of the sphere without resolution clustering, and on the other hand they provide the freedom to intentionally cluster grid points in some region of interest. In this work we run ICON‐O on an uniform grid of approximately 10 km resolution and on a grid with four times less degrees of freedom that is stretched such that in the resulting telescoping grid within the North Atlantic the two resolutions are similar, while outside the focal area the grid approaches smoothly ∼80 km resolution. By comparison with observations and reanalysis data we show first, that the simulation on the uniform 10 km grid provides a decent mesoscale eddy rich simulation and second, that the telescoping grid is able to reproduce the mesoscale rich circulation locally in the North Atlantic and on decadal time scales. This telescoping technique of unstructured grids opens new research directions. Key Points: We describe Ico sahedral N onhydrostatic Weather and Climate Model (ICON‐O) the ocean component of ICON‐ESM 1.0, based on the ICON modeling framework ICON‐O is analyzed in a globally mesoscale‐rich simulation and in a telescoping configuration In telescoping configuration ICON‐O reproduces locally the eddy dynamics with less computational costs than the uniform configuration